Validating the Job Crafting Questionnaire (JCRQ): a multi-method and multi-sample study - Nielsen, K. (2017)
Job crafting presents one set of proactive behaviours that employees may engage in to alter the job content or their relations at work. In recent years, several measures have been developed to capture job crafting. In the present study, we test the validity and reliability of an existing job crafting questionnaire (JCRQ) in four studies: First, we test the scale validity of the JCRQ in a Spanish diary study (Spain, N = 164, diary occasions 820). Second, we test the scale validity across two Western (Spain, N = 164, UK, N = 109) and two Eastern cultures (China, N = 170, Taiwan, N = 165). Third, we test the test-rest reliability in a Spanish three-wave longitudinal sample (N = 191). Finally, we test the criterion validity using data from the four countries. Results confirm the presence of five independent job crafting dimensions: increasing challenging demands, decreasing social job demands, increasing social job resources, increasing quantitative demands, and decreasing hindrance job demands. The JCRQ shows acceptable testretest reliability, scale and criterion validity across the four studies.